1961
DOI: 10.1161/01.res.9.2.465
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Lung Volume and Pulmonary Vascular Resistance

Abstract: Ten experiments were conducted on anesthetized dogs ventilated with a Starling pump and breathing oxygen. While tidal volume, respiratory rate, and arterial pH and pCO 2 were kept constant, lung volume was varied by using either a negative, zero, or positive end-expiratory pressure, leading to average changes in lung volume of -32, 0, and +75 per cent. Pulmonary vascular resistance (PVR) increased with either decreased or increased lung volume, indicating that the relationship between r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1962
1962
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…A clearly significant rise of PVR might have been prevented by manual lung inflation. Bo and Hognestad [4] have shown that platelet-induced pulmonary hypertension can be reversed by lung inflation, and Simmons et al [20] demonstrated a normalization of elevated PVR values when atelectatic lungs were reexpanded.…”
Section: Discussionmentioning
confidence: 99%
“…A clearly significant rise of PVR might have been prevented by manual lung inflation. Bo and Hognestad [4] have shown that platelet-induced pulmonary hypertension can be reversed by lung inflation, and Simmons et al [20] demonstrated a normalization of elevated PVR values when atelectatic lungs were reexpanded.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this notion explained the changes in pulmonary vascular resistance on the basis of physical alteration of the pulmonary blood vessels. Stretching or narrowing of vessels because of increased lung volume, or compression because of decreased lung volume can contribute [45][46][47]. Regional hypoxia develops in atelectatic lungs, however, and it has been shown that the mechanism of increased large vessel pulmonary vascular resistance in the lungs is due to hypoxic pulmonary vascular resistance, due in turn to decreased alveolar and mixed venous oxygen tension [48][49][50].…”
Section: Increased Pulmonary Vascular Resistancementioning
confidence: 99%
“…The lung volume was reported to be one of the factors in the distribution of pulmonary blood fl ow. Simmons et al [10], in an animal study, showed that the pulmonary vascular resistance increased when the lung was diminished in volume below the functional residual capacity. This fi nding has not been confi rmed in humans.…”
Section: Discussionmentioning
confidence: 99%